A citation analysis of the Philippine Law Journal on foreign and international law sources (2000-2012) towards a collection-related library approach of the University of the Philippines Law Library - Sandoval, Eunice S. (School of Library and Information Studies, University of the Philippines Diliman, 2013)
A law librarian should be able to provide the most effective materials to answer user needs. In a time where library budgets are getting smaller and library materials are getting more expensive, a law librarian should have a collection-oriented library approach to quantitatively assess the strength of his/her law library collection. One of the methods of this approach is citation analysis.